1995
DOI: 10.1074/jbc.270.26.15664
|View full text |Cite
|
Sign up to set email alerts
|

Myogenic Regulatory Factors Can Activate TATA-containing Promoter Elements via an E-Box Independent Mechanism

Abstract: We have studied the effect of several myogenic regulatory factors on the activity of the promoter for a mouse gene encoding a skeletal myosin heavy chain (MyHC) expressed in adult (type IIB) muscle fibers. Co-transfection of myogenic factors is necessary for activity of the IIB promoter in mouse C2 myotubes in culture but not in quail myotubes in culture. Although this promoter contains one E-box within the first 192 base pairs upstream of the transcriptional start site, mutations in this motif demonstrate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 50 publications
0
43
0
1
Order By: Relevance
“…TATAIIB, the small PstI͞XbaI fragment of 40IIB-MyHC-CAT (ref. 24; kindly provided by Thierry Diagana, Institut Pasteur, Paris) was inserted into SVP-Luci. The NRSE oligonucleotide was then inserted into the NotI͞PstI sites to obtain NRSE-TATAIIB.…”
Section: Methodsmentioning
confidence: 99%
“…TATAIIB, the small PstI͞XbaI fragment of 40IIB-MyHC-CAT (ref. 24; kindly provided by Thierry Diagana, Institut Pasteur, Paris) was inserted into SVP-Luci. The NRSE oligonucleotide was then inserted into the NotI͞PstI sites to obtain NRSE-TATAIIB.…”
Section: Methodsmentioning
confidence: 99%
“…Both the distance between the E box and the TATA box and the distance from the mRNA start site have been shown to be important for transactivation of the desmin promoter by MyoD and myogenin (30). Therefore, it is possible that direct interactions between myogenin and the basal transcription machinery, potentially mediated by TATA-binding protein-associated factors (TAFs) specifically expressed in differentiated myotubes (31), depend on restricted spatial requirements that are crucial for caveolin-3 gene transcription.…”
Section: Fig 3 Promoter Sequence and Mrna Start Site Of The Human Cmentioning
confidence: 99%
“…Transcriptional Activity of the IIB MyHC Promoter Requires MEF-2 Binding to mAT1 and Oct-1 or MEF-2 Binding to mAT2-We have previously demonstrated that the presence of the mAT1 site or the mAT1 plus mAT2 sites leads to an increased level of transcriptional activation when included in reporter gene plasmid constructions used for transient transfection assays in quail myotubes (12) and C2 myotubes (10). (Note that in order for the IIB MyHC promoter to be active in C2 myogenic cells, co-transfection with an expression vector for one of the myogenic bHLH factors is necessary; this system has been analyzed and validated in our laboratory (10,39).)…”
Section: Figmentioning
confidence: 99%
“…(Note that in order for the IIB MyHC promoter to be active in C2 myogenic cells, co-transfection with an expression vector for one of the myogenic bHLH factors is necessary; this system has been analyzed and validated in our laboratory (10,39).) The 192-bp construct (Ϫ192 bp/ϩ13 bp of the IIB MyHC promoter immediately upstream of the CAT reporter gene), containing both mAT sites, is the most active of all the promoter constructs, even including those which are much larger (e.g.…”
Section: Figmentioning
confidence: 99%